Gambaran Pengetahuan Ibu Hamil Tentang Pemeriksaan Triple Eliminasi Di Puskesmas Hutaimbaru - LUBIS, ARISA HARFA SAID; Nur Arfah Nasution; Fatma Mutia; Anwar Syahadat; Sukhri Herianto Ritonga; Mei Adelina Harahap; Nur Aliyah Rangkuti (Jurnal Kesehatan Ilmiah Aufa Royhan, 2025)
The Maternal Mortality Rate (MMR) is one indicator in determining the level of public health. Maternal deaths due to infection can be caused by several factors, including reproductive tract infections and sexually transmitted diseases such as Human Immunodeficiency Virus (HIV), Syphilis, and Hepatitis B. Prevention efforts for these diseases can begin while the baby is still in the womb through Triple Elimination screening. Triple Elimination aims to stop the transmission of HIV, Syphilis, and Hepatitis B from mother to child, reducing morbidity, disability, and mortality by conducting screenings for pregnant women. Prevalence rates in Indonesia for these three diseases indicate a risk of HIV transmission in pregnant women of 0.3%, syphilis infection in pregnant women of 1.7%, and hepatitis B infection in pregnant women of 2.5%. The purpose of this study was to determine the level of knowledge of pregnant women regarding triple elimination screening. The research method used was quantitative with a descriptive design. The study was conducted at the Hutaimbaru Community Health Center, involving all 52 pregnant women attending the center. The results showed that 26 respondents (50%) had poor knowledge regarding triple elimination screening, 14 respondents (26.9%) had sufficient knowledge, and 12 respondents (23.1%) had good knowledge. Therefore, the knowledge of pregnant women regarding triple elimination screening in Hutaimbaru Community Health Center is largely inadequate (50%). The results of this study recommend more creative outreach programs to encourage pregnant women to undergo triple elimination screening. Keywords : Knowledge, Triple Elimination, Pregnant Women